Sector-wise Impact of Film Induced Tourism over National Economic Perspective - Sriganeshvarun N , Dr Jayaprakash D (International Journal of Advanced Science and Technology, 2020)
Indian film Industry is also termed as Bollywood which is world-famous for its epic drama and storyline. The shooting locations used in movies are adventurous beautiful and memorable [3]. As per the report of recent surveys by champion traveller organization. A famous movie can push up the tourism of the film location from a minimum of 25% to a maximum of 300%. Tourism is the industry which can revitalise the nation’s economy to a much favourable extent. The survey states some popular movies which boosted the tourism sector to a higher notch. Braveheart - 300% increase in the tourism of Scotland’s, Wallace Monument. Harry Potter - 50% increase in the tourism of all filming locations, in most places the increase was as higher as 200%. Mission Impossible 2 - 200% in the tourism of Sidney’s National Park. Troy - 73% in the tourism of Turkey’s Canakkale. There are several other locations to discuss worldwide. The essence of all the above data records is, films have a vast impact over the tourism sector and tourism has a directly proportional relationship with the country’s economy [5]. In this paper, we discuss cinema induced tourism in the Indian context by learning the experiences from worldwide movie industries. We discuss different regional film industries and their contribution over-tourism, the lagging and leading Indian film industry based on tourism context. We also discuss the recent plans and subsidies provided by the Indian government to film producers to encourage national and international movies shooting in India. The worldwide movie fraternity contribution and benefits in terms of tourism is widely discussed.